Is Targeting Inflammation the Key to Unlocking HFpEF?: Focus on anti-inflammatory therapy - Yurista, Salva Reverentia; Sargowo, Djanggan (Universitas Brawijaya, 2024)
Chronic inflammation plays a crucial role in the formation of atherosclerosis and is also associated with the advancement of heart failure. Clinical and epidemiological evidence has increasingly supported the link between low-grade inflammation and heart failure with preserved ejection fraction (HFpEF). From a fundamental scientific standpoint, inflammation in HFpEF has notable detrimental impacts on the endothelium and the microvasculature of the heart. HFpEF clinical studies focusing on inflammation are a sign of hope because they show a shift toward treating the condition's cause instead of just its symptoms.